2015
DOI: 10.1016/j.jaci.2015.03.023
|View full text |Cite
|
Sign up to set email alerts
|

Magnitude of effect of asthma treatments on Asthma Quality of Life Questionnaire and Asthma Control Questionnaire scores: Systematic review and network meta-analysis

Abstract: The established within-patient MID for the ACQ and AQLQ is not achievable as a group-wise efficacy threshold between treatment arms in clinical studies in which controllers are added to ICS treatment. Thus in addition to reporting mean changes of the instruments, other measurement criteria should be considered, including responder analyses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
58
1
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 58 publications
(65 citation statements)
references
References 25 publications
5
58
1
1
Order By: Relevance
“…[27][28][29] It is likely that patients became more adherent to background ICS therapy during the course of the trial, a well-known phenomenon in clinical trials in this age group. 26 The results of our study add to the body of evidence that supports the inclusion of tiotropium as an option in the stepwise addition of treatment for uncontrolled asthma in adolescents. According to current guidelines, the addition of a LABA should be considered in adolescent patients with mild or moderate asthma not fully controlled by ICS monotherapy, with a higher dose of ICS or the addition of an LTRA as acceptable alternatives.…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…[27][28][29] It is likely that patients became more adherent to background ICS therapy during the course of the trial, a well-known phenomenon in clinical trials in this age group. 26 The results of our study add to the body of evidence that supports the inclusion of tiotropium as an option in the stepwise addition of treatment for uncontrolled asthma in adolescents. According to current guidelines, the addition of a LABA should be considered in adolescent patients with mild or moderate asthma not fully controlled by ICS monotherapy, with a higher dose of ICS or the addition of an LTRA as acceptable alternatives.…”
Section: Discussionsupporting
confidence: 57%
“…Improvements in ACQ-6, ACQ-7, and AQLQ(S)112 scores were observed but were not statistically significant compared with those in patients receiving placebo; however, the study was not powered for these end points. Furthermore, in a network analysis of results from a large number of asthma trials in which ACQ and AQLQ scores were assessed, Bateman et al 26 reported that the minimal clinically important difference (expressed as mean improvements between treatment arms) is seldom achieved and unlikely in studies like ours, in which a second or third controller is added in combination with ICSs. A limitation of our study might be the relatively large response observed in the placebo group.…”
Section: Discussionmentioning
confidence: 73%
“…ICS/LABA combination therapy results in improved lung function and control of symptoms compared with monotherapy with either drug [3-5]. As such, these two classes of drugs are now available in several fixed-dose combinations.…”
Section: Introductionmentioning
confidence: 99%
“…At study's end, although not statistically significant between treatments, the mean overall improvement (reduction) in ACQ-7 score from baseline in patients receiving montelukast plus roflumilast in period 2 almost achieved the minimal clinically important difference for an ACQ-7 score of 0.5, a surprising result given the difficulty of achieving this in studies of add-on therapy in asthmatic patients. 24 A post hoc responder analysis confirmed a decrease of 0.5 or greater in ACQ-7 score in only 1 of the 2 treatment periods with roflumilast plus montelukast (15 patients) compared with 8 patients receiving placebo plus montelukast. Reliever medication use was also lower while patients were taking roflumilast plus montelukast than while taking placebo plus montelukast.…”
Section: Discussionmentioning
confidence: 86%